Synthesis, self‐assembly, and formation of photo‐crosslinking‐stabilized fluorescent micelles covalently containing zinc(II)‐bis(8‐hydroxyquinoline) for ABC triblock copolymer bearing cinnamoyl and 8‐hydroxyquinoline side groups. Issue 8 (20th October 2015) - Wang, Wenjuan; Lin, Ling; Lu, Jiang; Liang, Hui; Feng, Hao; Hu, Lifen
ABSTRACT: Triblock copolymers (MPEG‐ b ‐PCEMA‐ b ‐PHQHEMA) bearing cinnamoyl and 8‐hydroxyquinoline side groups with different block length are synthesized by a two‐step reversible addition fragmentation chain transfer polymerization of cinnamoyl ethyl methacrylate (CEMA) and 2‐((8‐hydroxyquinolin‐5‐yl)methoxy)ethyl methacrylate (HQHEMA), respectively. The self‐assembly of MPEG‐ b ‐PCEMA‐ b ‐PHQHEMA in mixture of THF and ethanol is investigated by varying the ratio of THF and ethanol. Spheric micelles with diameter of 63.7 nm and polydispersity of 0.128 are obtained for MPEG113 ‐ b ‐PCEMA15 ‐ b ‐PHQHEMA17 in THF/ethanol with a volume ratio (v/v) of 5/5. The PCEMA inner shell of the resulted micelles is photo‐crosslinked under UV radiation to give stabilized micelles. The complex reaction of the stabilized micelles with Zn(II) is investigated under different conditions to give zinc(II)‐bis(8‐hydroxyquinoline)(Znq2 )‐containing micelles. When the complex reaction is carried out in THF/ethanol (v/v = 5/5) or THF/toluene (v/v = 6/4) with zinc acetate, fluorescent Znq2 ‐containing micelles are obtained without obvious change in diameters and morphologies. The fluorescent micelles exhibit green emission with λ max at 520 nm. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1056–1064 Abstract : Triblock copolymer MPEG‐ b ‐PCEMA‐ b ‐PHQHEMA was synthesized via a two‐step RAFT polymerization. The triblock copolymer can self‐assemble into micelles in mixture solvent of THF and ethanol. The self‐assembly micelles were stabilized by photo‐crosslinking of the PCEMA inner shell under UV irradiation. Fluorescent Znq2 ‐containing stabilized micelles were obtained by complex reaction of stabilized micelles with zinc acetate in mixture solvent of THF/ethanol or THF/toluene, exhibiting intensive green emission with λ max at 520 nm.